The use of indigenous plants as food by a rural community in the Eastern Cape: Tuku 'A' Village, Peddie - Soul Shava (Environmental Association of Southern Africa, 1999)
In this short contribution the author, a Masters in Environmental Education student, introduces his research into a rural community's knowledge about, attitudes towards and extensive use of plants which grow wild in their locality, with specific reference to their diet. Taking an ethnographic approach to the study of people's relationships with plants, Shava spent a number of weeks in a village in Peddie, South Africa. Here he learned that some young people still know much about wild plants and their uses, but that these plants are playing a decreasing role in their diets. He attributes the growing negative attitudes towards wild plants to modernisation, the non-supportive role of formal education, and advertising which encouraged people to rely on store-bought foods. Environmental educators should consider paying greater attention to the role of "wild" foods in the diet. Such attention can contribute not only to the conservation of biodiversity, but also to greater food security and health.